2008
DOI: 10.1016/j.bbamcr.2008.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and yeast apoptosis

Abstract: Apoptosis is associated in many cases with the generation of reactive oxygen species (ROS) in cells across a wide range of organisms including lower eukaryotes such as the yeast Saccharomyces cerevisiae. Currently there are many unresolved questions concerning the relationship between apoptosis and the generation of ROS. These include which ROS are involved in apoptosis, what mechanisms and targets are important and whether apoptosis is triggered by ROS damage or ROS are generated as a consequence or part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
268
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(275 citation statements)
references
References 172 publications
6
268
0
1
Order By: Relevance
“…An excess of ROS can cause damage to numerous cellular components, including nucleic acids and lipids. In recent years, it has become evident that ROS also play an important signaling role controlling and regulating some biological processes, such as growth, development, response to biotic and abiotic environmental stimuli and programmed cell death (Perrone et al 2008;Scott and Eaton 2008). To control ROS toxicity and to enable ROS to act as signaling molecules, cells have developed a variety of antioxidant systems to efficiently scavenge ROS excess and to keep ROS production and scavenging systems in balance.…”
Section: Introductionmentioning
confidence: 99%
“…An excess of ROS can cause damage to numerous cellular components, including nucleic acids and lipids. In recent years, it has become evident that ROS also play an important signaling role controlling and regulating some biological processes, such as growth, development, response to biotic and abiotic environmental stimuli and programmed cell death (Perrone et al 2008;Scott and Eaton 2008). To control ROS toxicity and to enable ROS to act as signaling molecules, cells have developed a variety of antioxidant systems to efficiently scavenge ROS excess and to keep ROS production and scavenging systems in balance.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse studies have shown that apoptotic cells can be a source of ROS, and therefore of oxidative damage (Perrone et al, 2008). Consequently, we determined protein carbonylation in aif1 cells after 24 h of selenite treatment, compared with wild-type cells.…”
Section: Selenite Provokes An Increase Of Protein Carbonylationmentioning
confidence: 99%
“…Oxidative stress is among the apoptosis inducers in yeast (Perrone et al, 2008). Thus, hydrogen peroxide at low concentrations provokes apoptosis in a process dependent on the metacaspase Yca1p and on a functional mitochondrial respiratory chain, while high peroxide concentrations provoke non-apoptotic death (Khan et al, 2005;Madeo et al, 1999Madeo et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation of the molecular mechanisms involved in this process showed that a chronic decrease in ATP/ADP⅐P i ratio induced an increase in the intracellular glutathione redox state. Cellular mechanisms that maintain redox homeostasis are crucial, because they provide a buffer against conditions that may perturb the redox environment of cells and/or induce oxidative stress (36,39,40). The abundance of glutathione (1-10 mM) in cells and its low redox potential (Ϫ240 mV) make the glutathione system a major intracellular redox buffer in most cells (36,41,42).…”
Section: Discussionmentioning
confidence: 99%